Community composition of coral-associated Symbiodiniaceae differs across fine-scale environmental gradients in Kāne‘ohe Bay - Mariana Rocha de Souza; Carlo Caruso; Lupita Ruiz-Jones; Crawford Drury; Ruth Gates; Robert J. Toonen (Royal Society Open Science, 2022)
The survival of most reef-building corals is dependent upon a symbiosis between the coral and the community of Symbiodiniaceae. Montipora capitata, one of the main reef-building coral species in Hawai'i, is known to host a diversity of symbionts, but it remains unclear how they change spatially and whether environmental factors drive those changes. Here, we surveyed the Symbiodiniaceae community in 600 M. capitata colonies from 30 sites across Kāne'ohe Bay and tested for host specificity and environmental gradients driving spatial patterns of algal symbiont distribution. We found that the Symbiodiniaceae community differed markedly across sites, with M. capitata in the most open-ocean (northern) site hosting few or none of the genus Durusdinium, whereas individuals at other sites had a mix of Durusdinium and Cladocopium. Our study shows that the algal symbiont community composition responds to fine-scale differences in environmental gradients; depth and temperature variability were the most significant predictor of Symbiodiniaceae community, although environmental factors measured in the study explained only about 20% of observed variation. Identifying and mapping Symbiodiniaceae community distribution at multiple scales is an important step in advancing our understanding of algal symbiont diversity, distribution and evolution and the potential responses of corals to future environmental change.